Research on tensile fracture process of polyester woven fabric based on AE technique and HHT - Yajing XUE; Lantian LIN; Cong GAO; Shuhua LIU (Journal of Hebei University of Science and Technology, 2016)
In order to obtain and study time-frequency characteristics of fabric tensile failure modes, four kinds of fabrics is woven with changing different fabric organizational structures and weft densities, dynamic audio signals for different fabrics in tensile failure process is collected with the aid of self-built acoustic emission detection system on the conventional fabric tensile tester, and the collected signal is analyzed and processed by using Matlab software to run a program compiled based on Hilbert Huang transform. The results show that AE signal curve is completely corresponding to tensile load-displacement curve in fabric tensile process, and characterizations of three failure modes about structure change, yarn deformation, and yarn fracture can be clearly distinguished. The characteristic frequency of four kinds of fabrics in structure change stage is the same as 100 Hz, which can be derived from the same source (orthogonal friction of yarns), and has nothing to do with the fabric organizational structure or density. The structure change stage has something to do with yarn strength utilization in such aspects as the AE signals characteristics of duration, amplitude, energy, and so on.